Diet as a therapeutic tool in chronic gastrointestinal disorders: Lessons from the FODMAP journey. Issue 4 (18th January 2022) - Gibson, Peter R; Halmos, Emma P; So, Daniel; Yao, Chu K; Varney, Jane E; Muir, Jane G
Abstract: Background and Aim: Diet is a powerful tool in the management of gastrointestinal disorders, but developing diet therapies is fraught with challenge. This review discusses key lessons from the FODMAP diet journey. Methods: Published literature and clinical experience were reviewed. Results: Key to designing a varied, nutritionally adequate low‐FODMAP diet was our accurate and comprehensive database of FODMAP composition, made universally accessible via our user‐friendly, digital application. Our discovery that FODMAPs coexist with gluten in cereal products and subsequent gluten/fructan challenge studies in nonceliac gluten‐sensitive populations highlighted issues of collinearity in the nutrient composition of food and confirmation bias in the interpretation of dietary studies. Despite numerous challenges in designing, funding, and executing dietary randomized controlled trials, efficacy of the low‐FODMAP diet has been repeatedly demonstrated, and confirmed by real‐world experience, giving this therapy credibility in the eyes of clinicians and researchers. Furthermore, real‐world application of this diet saw the evolution of a safe and effective three‐phased approach. Specialist dietitians must deliver this diet to optimize outcomes as they can target and tailor the therapy and to mitigate the key risks of compromising nutritional adequacy and precipitating disordered eating behaviors, skills outside the gastroenterologist's standard tool kit. While concurrent probiotics are ineffective, specific fiber supplements may improve short‐term and long‐term outcomes. Conclusions: The FODMAP diet is highly effective, but optimal outcomes are contingent on the involvement of a gastroenterological dietitian who can assess, educate, and monitor patients and manage risks associated with implementation of this restrictive diet.